ANALISIS PENGARUH KECUKUPAN MODAL, EFISIENSI, LIKUIDITAS, NPL, DAN PPAP TERHADAP ROA BANK - Krisna Hidajat (Majalah Ilmiah Bijak, 2017)
This research  is performed  in order  to test the influence  of  the  variable, Capital Adequacy Ratio (CAR), Biaya Operasi terhadap Pendapatan Operasi (BOPO), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Pembentukan Penyisihan Aktiva Produktif (PPAP) toward Return on Asset (ROA).Methodology reseach as the sample used sensus. Sample was accuired 23 banking company listed in JSX over period 2010-2013. Data analysis with multi linear regression of ordinary least square and hypotheses test used t-statistic dan F-statistic at level of significance  5%, a classic assumption  examination  which consist  of data  normality  test,  multicolinierity  test,  heteroskedasticity  test  and autocorrelation test is also being done to test the hypotheses.During research  period show' as variable and data research was normal distributed.  Based  on  multicolinierity  test,  heteroskedasticity  test  and autocorrelation test classic assumption deviation has not founded, tihis indicate that the available data has fulfill  the condition to use multi linear regression model. Empirical evidence show as CAR. BOPO and LDR toward ROA banking listed in JSX over period 2010-2013  at level of significance less than 5% (as 0,01%,0,01% and 0,6% each). While,  two  independent  variable  NPL,  and PPAP  not influence toward R0A at level of significance more than 5% at 88,2% and 72,7%. Where it was proved that together this research is performed in order to test the influence  of the variable  CAR,  BOPO,  LDR,  NPL and PPAP  to have influence toward banking ROA in JSX at level less than 5% (with level of significance 0,05). Prediction capability from these seven variable toward ROA is 35,1% where the balance (64,9%) is affected to other factor which was not to be entered to research model.